Real-World Outcomes and Factors Associated With the Second-Line Treatment of Patients With Gastric, Gastroesophageal Junction, or Esophageal Adenocarcinoma. (3rd May 2019) - Barzi, Afsaneh; Hess, Lisa M.; Zhu, Yajun E.; Liepa, Astra M.; Sugihara, Tomoko; Beyrer, Julie; Chao, Joseph
This retrospective observational study was designed to evaluate overall survival in a real-world patient population and to identify predictive factors associated with receipt of second-line therapy. A retrospective analysis of electronic medical records (Flatiron Health, New York) was conducted among patients initiating first-line therapy from January 1, 2013, through April 30, 2018. Eligible patients were diagnosed with advanced gastric, gastroesophageal junction, or esophageal adenocarcinoma and ≥18 years of age at the time of treatment initiation. Patients alive 45 days after discontinuation of first-line therapy were considered potentially eligible for continued therapy and were categorized into those who received and those who did not receive second-line therapy. Survival analyses were conducted using Kaplan-Meier method and log-rank test without adjusting for any baseline covariates. Factors associated with further treatment were evaluated using logistic regression. A total of 3850 patients met eligibility criteria. Among the 2516 patients available to receive second-line therapy, 1515 (60.2%) received second-line therapy and 1001 (39.8%) did not receive further therapy. Among those potentially eligible to receive second-line therapy, median survival was 15.4 months (95% confidence interval [CI]: 14.6-16.0) from initiation of first-line therapy for those who received second-line therapy and 10.0 months (95% CI: 9.3-10.7) for those who did not. Longer duration of first-line therapy (≥169 vs ≤84 days), HER2-positive tumors, initially diagnosed with stage IV disease, less weight loss during first-line therapy, and younger age were associated with receipt of second-line therapy (all P < .001). Longer survival was associated with multiple lines of therapy; however, these results should be interpreted with caution, and no causal relationship can be inferred.